A Three‐Dimensional Porous Organic Semiconductor Based on Fully sp2‐Hybridized Graphitic Polymer. Issue 35 (11th June 2020) - Byun, Yearin; Xie, Lilia S.; Fritz, Patrick; Ashirov, Timur; Dincă, Mircea; Coskun, Ali
Abstract: Dimensionality plays an important role in the charge transport properties of organic semiconductors. Although three‐dimensional semiconductors, such as Si, are common in inorganic materials, imparting electrical conductivity to covalent three‐dimensional organic polymers is challenging. Now, the synthesis of a three‐dimensional π‐conjugated porous organic polymer (3D p‐POP) using catalyst‐free Diels–Alder cycloaddition polymerization followed by acid‐promoted aromatization is presented. With a surface area of 801 m 2  g −1, full conjugation throughout the carbon backbone, and an electrical conductivity of 6(2)×10 −4  S cm −1 upon treatment with I2 vapor, the 3D p‐POP is the first member of a new class of permanently porous 3D organic semiconductors. Abstract : 3D p‐POP ! A 3D π‐conjugated porous organic polymer incorporating in situ formed pentacene linkers was synthesized through a catalyst‐free Diels–Alder cycloaddition polymerization and an acid‐promoted aromatization reaction. The resulting polymer shows high electrical conductivity and is the first member of a class of permanently porous 3D organic semiconductors.